The Review of Build-Own-Operate (BOO) for New and Renewable Power Plant under Minister of Energy and Mineral Resources Republic of Indonesia Regulation Number 4 of 2020 Based on the 1945 Indonesian Constitution - Rachim, Faiq Rizqi Aulia (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2022)
The government has issued Minister of Energy and Mineral Resources Republic of Indonesia Regulation Number 4 of 2020 that provides the build-own-operate (BOO) scheme which causes polemics in relation to the 1945 Constitution, especially the control of the state on vital means of production. This research is based on literary and regulatory studies. BOO is a scheme that waive the transfer stage where the Independent Power Producer hold ownership of the power plant. This scheme causes the reduce control of the government and limited transfer of technology. Despite this fact, the BOO scheme may attract investors due to having permanent ownership. The missing transfer stage signifies an unbundling practice in electricity suppliance. However, the 1945 Constitution mandates that the control of the state can be conducted through policies that prioritize the state and public welfare. Therefore, the BOO policy is not inconsistent to the 1945 Constitution